Giant Polarization in Quasi‐Adiabatic Ferroelectric Na+ Electrolyte for Solid‐State Energy Harvesting and Storage. (21st December 2022) - Carvalho Baptista, Manuela; Khalifa, Hesham; Araújo, Adão; Maia, Beatriz Arouca; Souto, Manuel; Braga, Maria Helena
Abstract : The advent of new solid‐state energy storage devices to tackle the electrical revolution requires the usage of nonlinear behavior leading to emergent phenomena. The ferroelectric analyzed herein belongs to a family of electrolytes that allow energy harvesting and storage as part of its self‐charging features when thermally activated. The Na2.99 Ba0.005 ClO electrolyte shows quasi‐adiabatic behavior with a continuous increase in polarization upon cycling, displaying almost no hysteresis. The maximum polarization obtained at a weak electric field is giant and similar to the remanent polarization. It depends on the temperature with a pyroelectric coefficient of 5.37 C m −2 °C −1 from −5 to 46 °C. The emergence occurs via negative resistance and capacitance. The glass transition is found to have its origins in the sharp depolarization at 46 – 48 °C. Above –10 °C, at ≈ –5 °C, another thermal anomaly may rely on the topologic characteristics of the A3–2x Bax ClO (A = Li, Na, K) glass electrolytes enabling positive feedback of the current of electrons throughout the surface of the inner cell. The phenomena may pave the way toward a better understanding of dipolar nanodomain fragile glasses with exceptional ferroelectric characteristics to architect energy harvesting and storage devices based on multivalent thermally activated Na + ‐ion‐ion electrolytes. Abstract : M. C. Baptista, H. Khalifa, A. Araújo, B. A. Maia, M. Souto, M. H. Braga Na + ‐based ferroelectric electrolyte with quasi‐adiabatic giant polarization features revealed; to be used in positive feedback tandem energy harvesting and storage devices performing at practical temperatures where other devices are not efficient.